2019
DOI: 10.1093/tropej/fmz067
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Five Conditions in a Tertiary Care Government Hospital in Bengaluru, South India—Three Years Experience

Abstract: Purpose Newborn screening is the need of the hour in a developing country like India as there is paucity of data from studies conducted in government hospitals with large sample size. The purpose of the study is to estimate incidence rate and recall rates for five conditions screened in the neonatal period namely congenital hypothyroidism, congenital adrenal hyperplasia, glucose-6-phosphate dehydrogenase (G6PD) deficiency, galactosemia and phenyl ketonuria (PKU). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Seventy-nine studies were included in the systematic review, and 70 studies in the meta-analysis. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 The flow...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventy-nine studies were included in the systematic review, and 70 studies in the meta-analysis. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 The flow...…”
Section: Resultsmentioning
confidence: 99%
“…Timing: 24-48 h; NICU admission- beyond 7 days age; premature- close to 7 days age; immediately before any transfusion for sick neonates. TSH-based 18 Unclear 13 376 15 Kommalur 2019 25 Postnatal filter paper between 48 h - discharge TSH-based 20 Unclear 41 027 16 Verma P 2019 26 Postnatal filter paper after 24 h of birth or at discharge, whichever was later. Preterm- not later than 36 completed weeks of gestation or 14 days of life, whichever was later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we used data only from studies with a sample size ≥9500 in whom the criteria to diagnose CH were clear and appropriate. [ 3 4 5 6 7 8 9 10 11 12 13 14 15 16 ]…”
mentioning
confidence: 99%
“…[ 5 ] A study from a medical institution of the government sector in Bengaluru also reported a relatively lower prevalence (1:2735). [ 6 ] However, another study from a tertiary health care center of the private sector in Bengaluru that used a lower TSH cut-off (12 μIU/ml) to define screen positivity reported a relatively higher prevalence (1: 852). [ 7 ]…”
mentioning
confidence: 99%